Avaliação sobre o conhecimento em angioedema hereditário entre profissionais da saúde - Mastelaro, Larissa Pincerato (2024)
Introduction: Hereditary angioedema is a rare, debilitating and potentially fatal disease, characterized by recurrent attacks of angioedema that affect the subcutaneous and submucosal tissue of different organs of the body. It is underdiagnosed and often confused with other conditions. Objective: The objective of this study was to evaluate knowledge about hereditary angioedema among healthcare professionals. Material and Methods: A questionnaire containing demographic data and questions about knowledge of hereditary angioedema was administered to healthcare professionals from different specialties who could potentially come across patients with hereditary angioedema: anesthetists, dermatologists, dentists, gastroenterologists, gynecologists/obstetricians, otorhinolaryngologists and clinicians general. Results: Six hundred and thirty health professionals responded to the questionnaire, with one hundred questionnaires for each specialty, sixty for dentists and seventy for gastroenterologists. Conclusion: The level of knowledge about hereditary angioedema was reduced among health professionals, thereby confirming the lack of knowledge about this disease, as well as the need for increased awareness about it.